Trade Liberalisation and Insider Power: The Case of Brazil - Jorge Saba Arbache (University of Kent, Department of Economics, 1999)
This paper investigates the impact of market-oriented economic reforms on union behaviour in Brazil. Previous work shows that openness, deregulation and similar measures constrain union power. In contrast, our results show that insider power has increased in the more competitive environment since the implementation of the reforms in Brazil in the early 1990s. We argue that this is associated with the structure of wage bargaining, and with the low quality of the labour force. Unions take advantage of the higher demand for qualified workers in a more competitive economy by increasing wage pressure.
Keywords: F14; J31; J51; 330; Trade liberalisation; insider power; wage structure; wage dispersion; Brazil; Handelsliberalisierung; Wirtschaftsreform; Tarifverhandlungen; Insider-Outsider-Theorie; Lohnstruktur; Brasilien